EVALUASI PROGRAM PENGEMBANGAN BAHASA ASING - DODY KURNIAWAN (Jurnal Evaluasi Pendidikan, 2013)
Entering the global competition era, people need strategies to master foreign language. The objective of the evaluation on the foreign language development program in IHBS Junior High School (JHS) is to determine effectiveness of the program process and identify the problems that emerge. The evaluation model used is the CSE-UCLA which was initiated by Alkin. The evaluation was accomplished in several phases, namely: assessment program, planning program, implementation program, improvement program, and certification program. The research results show that the operational of the foreign language development program di IHBS Junior High school did not meet the qualification as the assigned standard.